Analytics of ordinary language in P. F. Strawson’s philosophy - Dzisko-Schumann, Marya R. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The purpose of the article is a philosophical analysis of P. F. Strawson’s contribution to the development of the problems of the linguistic branch of analytical philosophy, represented by the Oxford school of ordinary language. The relevance of the work is due to the need to rethink a number of ideas of analytical philosophy, in the context of the development of directions and strategies of modern philosophy, in particular, the strategy of communicative rationality. The author substantiates the thesis that one of the key tasks of the philosophy of P. F. Strawson was the analysis of ordinary language in the focus of its main function – the formation of descriptive structures of reality, which is not only the result of the interaction of consciousness and reality, but also represents the result of social conventions. The objective task of philosophy is to clarify the nature of ordinary language and its functions. One of the results of the analytics of ordinary language is that language has conventional nature, the essence of which is determined by a dynamically changing instrument of social constitution, a mediating form and a structural element that determines the fundamental conditions of communication.
Keywords: analytical philosophy; language; theory of speech acts; communication; communicative intention